Penggunaan Pendekatan Pembelajaran Saintifik dalam Meningkatkan Keaktifan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Katolik Sekolah Menengah Pertama Budi Murni 2 - Erikson Simbolon; Bram Sena Sinaga (Universitas Batanghari Jambi, 2023)
This article discusses the use of scientific learning models as a solution to increase student learning activeness in the subject of Catholic Religious Education at Budi Murni 2 Middle School. Education is a self-development activity through a teaching and learning process that aims to increase students' knowledge, insight, and experience. However, the facts show that many students are not active in the current learning process, including in Catholic religious subjects. This research is based on observational findings which show the low activity of students in learning Catholic religion at Budi Murni 2 Middle School. The conventional learning methods currently used by teachers have not been able to activate students optimally. Therefore, the use of a scientific learning model is proposed as a solution to increase the active learning of students. The scientific learning model is a learning approach that involves students actively and creatively in the learning process. In this model, students are invited to observe, ask questions, reason, associate, and communicate the concepts or material being studied. Through this approach, students are expected to be able to develop higher-order thinking skills and have a high enthusiasm for learning. Previous research also shows that the use of scientific learning models can increase the active learning of students. In the context of Catholic Religious Education subjects, a scientific approach can help students learn religious concepts more actively and creatively. Catholic religious teachers are required to activate students by designing interesting learning, implementing collaboration, and using appropriate learning media. In the context of Budi Murni 2 Middle School, this study aims to apply a scientific learning model in learning Catholic Religious Education. The results of the research are expected to provide concrete solutions to increase the active learning of students, so as to improve the quality and quality of learning in these schools.